1997
DOI: 10.1242/jcs.110.11.1325
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import of hnRNP A1 is mediated by a novel cellular cofactor related to karyopherin-β

Abstract: Heterogeneous nuclear ribonucleoprotein A1 contains a sequence, termed M9, that functions as a potent nuclear localization signal (NLS) yet bears no similarity to the well-defined basic class of NLSs. Here, we report the identification of a novel human protein, termed MIP, that binds M9 specifically both in vivo and in vitro yet fails to interact with non-functional M9 point mutants. Of note, the 101 kDa MIP protein bears significant homology to human karyopherin/importin-beta, a protein known to mediate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…RanGppNHp interacts with the concave surface of the N-terminal arch of Kapβ2 through two contact areas: the first involves the first four HEAT repeats, which interact with the switch I and switch II regions of Ran; the second involves the central HEAT repeats 7, 8 and the acidic loop, which interact with the 'basic patch' R4-R5 region of Ran. The structure of the Kapβ2-Ran complex, in combination with previous biochemical studies using Kapβ2 deletion mutants, also allowed assignment of the substrate binding site of Kapβ2 to the concave surface of its C-terminal arch (2,10,11). The Kapβ2-Ran structure strongly suggests an allosteric mechanism for GTPase-mediated substrate dissociation.…”
mentioning
confidence: 73%
“…RanGppNHp interacts with the concave surface of the N-terminal arch of Kapβ2 through two contact areas: the first involves the first four HEAT repeats, which interact with the switch I and switch II regions of Ran; the second involves the central HEAT repeats 7, 8 and the acidic loop, which interact with the 'basic patch' R4-R5 region of Ran. The structure of the Kapβ2-Ran complex, in combination with previous biochemical studies using Kapβ2 deletion mutants, also allowed assignment of the substrate binding site of Kapβ2 to the concave surface of its C-terminal arch (2,10,11). The Kapβ2-Ran structure strongly suggests an allosteric mechanism for GTPase-mediated substrate dissociation.…”
mentioning
confidence: 73%
“…(C) Volcano plots from the microarray analysis showing the number of genes for which expression was decreased (blue) or increased (red) by 1.5-fold or greater under the indicated conditions. siNAT10 and siCT treatment were transient ( 5 that defective nuclear import of TNPO1 cargo proteins including NUP153 (24) and hnRNPA1 (27) appeared to contribute to downstream phenotypic defects in HGPS cells, including abnormal nuclear pore assembly, chromatin disorganization, gene expression changes, and premature entry into senescence. Although previous studies had reported RanGTP gradient defects in cells from HGPS patients (9,10), the mechanism behind it was still unclear.…”
Section: Tnpo1 Dysfunction In Hgps Drives Nuclear Ran Defectsmentioning
confidence: 99%
“…In the nucleus, RanGTP binds to TNPO1 to stimulate release of the cargo (26). Among TNPO1 cargos, the most extensively characterized is the RNA binding protein heterogeneous nuclear ribonucleoprotein 1 (hnRNPA1) (27), which functions in several processes including mRNA biogenesis and promotion of transcription factor activity (28)(29)(30). NPC protein NUP153 is also a target for TNPO1-mediated nuclear import (24).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that many members of karyopherin β family can function in nuclear import without adaptor proteins (i.e., karyopherin α) and can bind directly to their substrates (24,25). One example of such karyopherin is transportin, which mediates nuclear import of hnRNP through recognition of the M9 domain (26)(27)(28). However, in most cases the specific NLSs directly interacting with the members of karyopherin β family have yet to be elucidated.…”
Section: Cellular Nuclear Import Machinerymentioning
confidence: 99%